If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2tan(2x) = 3tanx + 1 Remove parenthesis around (2x) 2ant * 2x = 3tanx + 1 Reorder the terms for easier multiplication: 2 * 2ant * x = 3tanx + 1 Multiply 2 * 2 4ant * x = 3tanx + 1 Multiply ant * x 4antx = 3tanx + 1 Reorder the terms: 4antx = 1 + 3antx Solving 4antx = 1 + 3antx Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3antx' to each side of the equation. 4antx + -3antx = 1 + 3antx + -3antx Combine like terms: 4antx + -3antx = 1antx 1antx = 1 + 3antx + -3antx Combine like terms: 3antx + -3antx = 0 1antx = 1 + 0 1antx = 1 Divide each side by '1ntx'. a = n-1t-1x-1 Simplifying a = n-1t-1x-1
| 4x-10=2x+50 | | 9/8-1/4-2/3 | | 3(2+y)-4=10 | | -5a+6=15 | | (5x+2y)(5x-2y)=25x^2-4y^2 | | (x-8)+(9x-2)+36=360 | | X-23=105 | | 13/15-7/10 | | 3w+7=16 | | -5a+6=12 | | 19x+6=44 | | 24-5x=24-9x | | 4=-16t^2+45t+6 | | 3y=4t/y^2 | | 42=-16t^2+60t+6 | | 3y=(4t/y~2) | | 45=-16t^2+60+6 | | 4x^2+32x=-23 | | 35=-16t^2+60+6 | | 3(x-2)+5(x-2)=15x | | -9x+y=52 | | 42=-16t^2+60+6 | | 26-r=2r+2 | | (3x+1)+55=x | | 40=-16t^2+60+6 | | -2(13-m)=(m-19)-6 | | 12r+30-72=0 | | 100x+7x=111.28 | | 129+3x=x | | 40=-16t^2+46+6 | | 2r+26=r-2 | | 42=-16t^2+46+6 |